PELAKSANAAN SURGICAL PATIENT SAFETY TERHADAP ADVERSE EVENTS PASCAOPERASI BEDAH DIGESTIF DI INSTALASI BEDAH RSUP DR. SARDJITO YOGYAKARTA - , Erikson Siagian ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Patient Safety is also one dimension of quality that is currently being the center of attention of health care practitioners in the national and global scale. World Health Organization (WHO) estimated that there were at least half a million deaths due to surgery that could have been prevented. Safe Surgery Saves Lives program introduced and studied surgical safety checklist as an attempt to patient safety and to reduce the number of deaths worldwide. The main purpose of the surgical safety checklist is to reduce the unexpected incidence in the operating room. Objective: To know how far is the implementation of surgical patient safety in digestive surgery and to find the relationship between the implementation of surgical patient safety that affect the digestive surgery postoperative adverse events in the central surgical installation of general hospital DR. Sardjito Yogyakarta. Method: This study was a prospective observational study with longitudinal study designs. The subject of this study was all patients who underwent digestive surgery in the period of December 2010 at the central surgical installation of general hospital DR. Sardjito Yogyakarta. Observations were carried out using a checklist instrument of surgical patient safety implementation and assessment of adverse events for 30 days postoperatively. The collected data were analyzed with univariate and bivariate approaches. Result: Stages Sign in: Installation of pulse oximetry function well and performed in all patients, the diagnosis of writing difficulties breathing was performed in all patients and infusion 2 pathway in patients who have a risk of bleeding as much as 83.3%. Stages Time Out: Operators who do re-confirm the identity of the patient before surgery by 68.2%, giving prophylactic antibiotic injection is less than 60 minutes before skin incision of 77.3%. Stages Sign out: the implementation of the calculation of the instrument by 50%, netting calculation of 29.5% and 29.5% for the calculation of the needle. Postoperative incidence of Adverse Events: The ILO found in 9.1%, coma> 24 hours of 2.3%, use of ventilator> 48 hours was found at 4.5%, of patients operated on without re-planned by 2.3%, bleeding requiring transfusion > 4 units of blood within 72 hours of 4.5% and mortality of 4.5%. Bivariate Analysis Results: There was a significant relationship (p = 0.016) between patients who have a risk of blood loss with the death, there is a significant relationship (p = 0.016) between patients who have a risk of blood loss with bleeding. Conclusion: Surgical Patient Safety Implementation had not yet being consistently implemented and the implementation of the Surgical Patient Safety was related with the occurrence of postoperative Adverse Events in digestive surgery in the DR. Sardjito Hospital installation.